High-Coverage Profiling of Hydroxyl and Amino Compounds in Sauce-Flavor Baijiu Using Bromine Isotope Labeling and Ultra-High Performance Liquid Chromatography–High-Resolution Mass Spectrometry - Zixuan Wang; Youlan Sun; Tiantian Chen; Lili Jiang; Yuhao Shang; Xiaolong You; Feng Hu; Di Yu; Xinyu Liu; Bo Wan; Chunxiu Hu; Guowang Xu (Metabolites, 2025)
Background: Hydroxyl and amino compounds play a significant role in defining the flavor and quality of sauce-flavor Baijiu, yet their comprehensive analysis remains challenging due to limitations in detection sensitivity. In this study, we developed a novel bromine isotope labeling approach combined with ultra-high performance liquid chromatography–high-resolution mass spectrometry (UHPLC-HRMS) to achieve high-coverage profiling of these compounds in sauce-flavor Baijiu. Methods: The method employs 5-bromonicotinoyl chloride (BrNC) for rapid (30 s) and mild (room temperature) labeling of hydroxyl and amino functional groups, utilizing bromine’s natural isotopic pattern (Δm/z = 1.998 Da) for efficient screening. Annotation was performed hierarchically at five confidence levels by integrating retention time, accurate mass, and MS/MS spectra. Results: A total of 309 hydroxyl and amino compounds, including flavor substances (e.g., tyrosol and phenethyl alcohol) and bioactive compounds (e.g., 3-phenyllactic acid), were identified in sauce-flavor Baijiu. The method exhibited excellent analytical performance, with wide linearity (1–4 orders of magnitude), precision (RSD < 18.3%), and stability (RSD < 15% over 48 h). When applied to sauce-flavor Baijiu samples of different grades, distinct compositional patterns were observed: premium-grade products showed greater metabolite diversity and higher contents of bioactive compounds, whereas lower-grade samples exhibited elevated concentrations of acidic flavor compounds. Conclusions: These results demonstrate that the established method is efficient for the comprehensive analysis of hydroxyl and amino compounds in complex food matrices. The findings provide valuable insights for quality control and flavor modulation in sauce-flavor Baijiu production.